2017
DOI: 10.5194/bg-2017-256
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glacial-Interglacial changes and Holocene variations in Arabian Sea denitrification

Abstract: <p><strong>Abstract.</strong> At present the Arabian Sea has a permanent oxygen minimum zone (OMZ) at water depths between about 100 m and 1200 m. Active denitrification in this OMZ is recorded by enhanced δ<sup>15</sup>N values in the sediments. Sediment cores show a δ<sup>15</sup>N increase from early to late Holocene which is contrary to the trend in other r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…This feedback mechanism might have played an important role in maintaining the hypoxic conditions within the Arabian Sea and Bay of Bengal OMZ by preventing the development of anoxic conditions. As discussed in the following chapters this also agrees with model and paleoceanographic results suggesting that variations of the physical oxygen supply rather than changes in the biological oxygen demand are drivers controlling the intensity of the OMZ in both the Arabian Sea and the Bay of Bengal (Gaye et al, 2018;McCreary Jr et al, 2013;Resplandy et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This feedback mechanism might have played an important role in maintaining the hypoxic conditions within the Arabian Sea and Bay of Bengal OMZ by preventing the development of anoxic conditions. As discussed in the following chapters this also agrees with model and paleoceanographic results suggesting that variations of the physical oxygen supply rather than changes in the biological oxygen demand are drivers controlling the intensity of the OMZ in both the Arabian Sea and the Bay of Bengal (Gaye et al, 2018;McCreary Jr et al, 2013;Resplandy et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…In contrast to the Bay of Bengal denitrification has prevailed in the Arabian Sea during the warm interstadials of the Pleistocene and during the entire Holocene as can be discerned from δ 15 N >6 ‰ with maxima of >11 ‰ (Agnihotri et al, 2003;Higginson et al, 2004;Kessarkar et al, 2018;Möbius et al, 2011;Pichevin et al, 2007). Productivity increased with the onset of the Holocene as the summer monsoon strengthened and monsoonal upwelling off Somalia and Oman commenced and became a permanent feature of the Holocene Arabian Sea (Böning et al, 2009;Gaye et al, 2018). A rise of δ 15 N by at least 2 ‰ shows that onset of upwelling immediately strengthened the OMZ and led to https://doi.org/10.5194/bg-2020-82 Preprint.…”
Section: Omz Fluctuations In the Holocenementioning
confidence: 99%
See 1 more Smart Citation
“…This study also finds an intensification of land-sea thermal and pressure gradients that is consistent with the Bakun (1990) hypothesis. Other studies reveal that summer monsoon wind intensification has already been observed recently (Goes et al, 2005;Wang et al, 2013). Goes et al (2005) reported an increase in upwelling-favorable winds off Somalia over the period between 1997 and 2005 and have shown an associated increase in productivity over the same period.…”
Section: Introductionmentioning
confidence: 98%
“…Other studies reveal that summer monsoon wind intensification has already been observed recently (Goes et al, 2005;Wang et al, 2013). Goes et al (2005) reported an increase in upwelling-favorable winds off Somalia over the period between 1997 and 2005 and have shown an associated increase in productivity over the same period. Wang et al (2013) found a global intensification of the Northern Hemisphere summer monsoon since the late 1970s and attributed these trends to the interaction of the mega El Niño-Southern Oscillation and the Atlantic Multidecadal Oscillation, in addition to hemispherical asymmetric global warming.…”
Section: Introductionmentioning
confidence: 98%